The Influence of Brand Image And Brand Equity On Brand Loyalty Through Brand Trust of Matic Motorcycle Users - Andrea Septa Nugraha; Enni Sustiyatik; Heru Marwanto (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2025)
This study aims to analyze the influence of brand image and brand equity on brand loyalty through brand trust of automatic motorcycle users. The population in this study is consumers in Kediri City who have bought or used Honda automatic motorcycles, while the sample is 127 people with simple random sampling. The type of research used is quantitative research with an associative descriptive approach. The data analysis method uses Path Analysis. Data collection was carried out by distributing questionnaires at Galaxy Motor dealers in Kediri City. The results of descriptive statistical analysis show that brand image is included in the criteria of good image, brand equity is included in the criteria of good brand equity, brand loyalty is included in the loyal criteria, brand trust is included in the criteria of trustworthiness. The results of the study show that (1) Brand image (X1) is proven to have a direct positive and significant effect on brand trust (Z). In (2) Brand equity (X2) is proven to have a direct positive and significant effect on brand trust (Z). Then (3) Brand trust (Z) is proven to have a direct positive and significant effect on brand loyalty (Y). Then (4) Brand image (X1) is proven to have a direct positive and significant effect on brand loyalty (Y). And in (5) Brand equity (X2) has been proven to have a direct positive and significant effect on brand loyalty (Y). And the last (6) There is a positive and significant indirect influence between brand image and brand equity on brand loyalty through brand trust in users of Honda automatic motorcycle products.